Field-Based Models of Primary Teacher Training: Case Studies of Student Support Systems from Sub-Saharan Africa - Mattson, Elizabeth (Department for International Development, 2006)
KerkoCite.ItemAlsoKnownAs: 2405685:48KESELW
Keywords: C:sub-Saharan Africa; ⛔ No DOI found

Paradigm Peace and the Implications for Quality - Bryman, Alan (International Journal of Social Research Methodology, 2006)
In this article it is shown that the paradigm wars that raged concerning the incompatibility of quantitative and qualitative research have largely subsided. In the process, discussions of epistemological and ontological issues have become less prominent. The peace that has broken out has proved to be more favourable to research combining quantitative and qualitative research than was the case during the paradigm wars. Drawing on interviews with social researchers who employ a mixed‐methods approach and on the literature, it is shown that a spirit of pragmatism with regard to combining quantitative and qualitative research prevails which encourages researchers to consider using mixed‐methods research when the research question is suited to it. However, the issue of which quality criteria should be employed in investigations combining quantitative and qualitative research has not been given a great deal of consideration. The author argues for a contingency approach, in which issues to do with quality are decided in relation to the nature of the study.
shortDOI: 10/b8wtt2 KerkoCite.ItemAlsoKnownAs: 10.1080/13645570600595280 10/b8wtt2 2339240:T3KNAFUP 2405685:RKS7ELJH

Universal Design for Learning: Is It for Everyone? - Rose, D; Meyer, A (2006)
Universal Design for Learning (UDL) stands at the forefront of contemporary efforts to create universal access to educational curricula for all students, including those with disabilities. The "universal" in UDL does not mean there is a single optimal solution for everyone. Instead, it underscores the need for flexible approaches to teaching and learning that meet the needs of different kinds of learners. In this first UDL Reader, Anne Meyer and David H. Rose, cofounders of CAST, the educational nonprofit that developed the UDL framework, bring together a collection of articles on the practical, classroom dimensions of the UDL revolution in education. The authors offer insights on learner differences, the capacities of new media in the classroom, and effective teaching and assessment practices. The volume also includes lessons from teacher professional development workshops, classroom-based research, and UDL practitioners themselves. A highly readable volume aimed particularly at school teachers and administrators, this book is also an uncommonly accessible introduction to UDL for all readers committed to creating improved and universal access to educational materials for all students. Following a preface (Anne Meyer and David H. Rose), this book contains the following chapters: (1) Applying Universal Design for Learning in the Classroom (Peggy Coyne, Patricia Ganley, Tracey Hall, Grace Meo, Elizabeth Murray, and David Gordon); (2) A UDL Case Story and Model Lesson: Reading Challenges in Geography and Social Studies (The Staff at CAST); (3) Frequent Questions about Universal Design for Learning (Grace Meo); (4) A Level Playing Field: UDL in the Classroom (Lani Harac); (5) Teacher Perspectives: UDL in the Elementary Classroom (Kirsten Lee Howard); (6) Teacher Perspectives: Strategy Instruction Goes Digital (Nicole Strangman); (7) Implications of Universal Design for Learning for Classroom Assessment (David H. Rose and Robert P. Dolan); (8) The Promise of New Learning Environments for Students with Disabilities (Bart Pisha and Skip Stahl); (9) Transforming the Textbook to Improve Learning (Skip Stahl); (10) Engaging the Text: Brain Research and the Universal Design of Reading Strategy Supports (David H. Rose and Bridget Dalton); and (11) Teaching Internet Literacy Strategies: The Hero Inquiry Project (Maya B. Eagleton, Kathleen Guinee, and Karen Langlais). An index is also included.
KerkoCite.ItemAlsoKnownAs: 2339240:RTHAM8C5 2405685:2IJJICCL